Endogenous THBD (Thrombomodulin) Mediates Angiogenesis in the Ischemic Brain—Brief Report. Issue 12 (December 2020) - Wenzel, Jan; Spyropoulos, Dimitrios; Assmann, Julian Christopher; Khan, Mahtab Ahmad; Stölting, Ines; Lembrich, Beate; Kreißig, Sara; Ridder, Dirk Andreas; Isermann, Berend; Schwaninger, Markus
Abstract : Objective: THBD (thrombomodulin) is part of the anticoagulant protein C-system that acts at the endothelium and is involved in anti-inflammatory and barrier-stabilizing processes. A recombinant soluble form of THBD was shown to have protective effects in different organs, but how the endogenous THBD is regulated during ischemia, particularly in the brain is not known to date. The aim of this study was to investigate the role of THBD, especially in brain endothelial cells, during ischemic stroke. Approach and Results: To induce ischemic brain damage, we occluded the middle cerebral artery of mice. We found an increased endothelial expression of Thbd in the peri-infarct area, whereas in the core of the ischemic tissue Thbd expression was decreased compared with the contralateral side. We generated a novel Cre/loxP-based mouse line that allows for the inducible deletion of Thbd specifically in brain endothelial cells, which worsened stroke outcome 48 hours after middle cerebral artery occlusion. Unexpectedly, we found no signs of increased coagulation, thrombosis, or inflammation in the brain but decreased vessel diameters and impaired angiogenesis in the peri-infarct area that led to a reduced overall vessel length 1 week after stroke induction. Conclusions: Endogenous THBD acts as a protective factor in the brain during ischemic stroke and enhances vessel diameter and proliferation. These previously unknown properties of THBD could offer new opportunities to affect vessel function after ischemia and thereby improve stroke outcome. Abstract : Supplemental Digital Content is available in the text.